An evaluation of dryland watershed development projects in India - Kerr, John M.; George, P. S.; Pangare, Ganesh; Pangare, Vasudha (International Food Policy Research Institute, 2000)
This study addresses three main research questions: 1) What projects are most successful in promoting the objectives of raising agricultural productivity, improving natural resource management and reducing poverty? 2) What approaches enable them to succeed? 3) What nonproject factors also contribute to achieving these objectives? The major hypotheses are that participatory approaches that devote more attention to social organization yield superior project impact, and that favorable economic conditions and good infrastructure also support better natural resource management and higher productivity.